Analisis Strategi Pengembangan Usaha dengan Metode Analisis SWOT pada PT. Nusantara Logistic Sejahtera - Ihza Aditama Samudra; Rusdi Hidayat Nugroho (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine the internal and external factors that affect the company, confirm the company's position and design alternative strategies for the company. This research uses the object of PT. Nusantara Logistics Sejahtera which is engaged in container expeditions. The sample was conducted using the method of observation and in-depth interviews with the company. To answer the existing problems, PESTEL analysis is carried out, identification of internal and external factors with SWOT analysis and formulating alternative business development strategies and the IE Matrix (Internal-External) to determine the company's position and obtain alternative strategy themes in making the SWOT matrix.